The struggle for national identity of Poles in the Grand Duchy of Cieszyn Since the mid-nineteenth century until 1918 = Walka o tożsamość narodową Polaków w Księstwie Cieszyńskim od połowy XIX wieku do 1918 roku - Miszewski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An important element in Polish history was the struggle for the national identity of Poles in the Duchy of Cieszyn since the second half of the nineteenth century to the end of the First World War. Conducted a large-scale policy designed to promote other non-Polish nationality. The Poles did not surrender and actively sought to maintain their national identity in the area.
Keywords: the Duchy of Cieszyn; Spring of Nations; national identity; Księstwo Cieszyńskie; Wiosna Ludów; tożsamość narodowa